2021
DOI: 10.1093/jrr/rrab093
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a prognostic model for non-lung cancer death in elderly patients treated with stereotactic body radiotherapy for non-small cell lung cancer

Abstract: This study sought to develop and validate a prognostic model for non-lung cancer death (NLCD) in elderly patients with non-small cell lung cancer (NSCLC) treated with stereotactic body radiotherapy (SBRT). Patients aged ≥65 diagnosed with NSCLC (Tis-4N0M0), tumor diameter ≤5 cm and SBRT between 1998 and 2015 were retrospectively registered from two independent institutions. One institution was used for model development (arm D, 353 patients) and the other for validation (arm V, 401 patients). To identify risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…However, only patient and tumour-related factors were retained in this multivariate model, precluding its use in treatment decision-making. Another model developed in Japan only included patient-related variables (age, performance status, body mass index and Charlson comorbidity index) to predict non-lung cancer death in an elderly cohort receiving definitive SABR [ 27 ]. In contrast to these models, we deliberately chose to include a potentially curable population of patients with stage I-III NSCLC who were managed heterogeneously in order to develop a prediction model which can help decision-making in the real world.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only patient and tumour-related factors were retained in this multivariate model, precluding its use in treatment decision-making. Another model developed in Japan only included patient-related variables (age, performance status, body mass index and Charlson comorbidity index) to predict non-lung cancer death in an elderly cohort receiving definitive SABR [ 27 ]. In contrast to these models, we deliberately chose to include a potentially curable population of patients with stage I-III NSCLC who were managed heterogeneously in order to develop a prediction model which can help decision-making in the real world.…”
Section: Discussionmentioning
confidence: 99%
“…The patient-related determinants most commonly included in NSCLC models are age, sex and performance status. While a poorer prognosis has been associated with older age [ 27 ] and male sex [ 8 ] overall findings have been inconclusive. In line with previous models, our study found no significant associations between age and sex on the survival outcomes of the study population [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite minimally invasive surgical techniques, elderly patients undergoing guideline‐recommended lung resection have a significantly higher operative mortality rate than younger patients (6.9% vs. 3.7%) 24–26 . Several reports have shown that SBRT is a safe and feasible treatment for elderly patients regarding treatment complications and oncological outcomes 18,27–38 . The use of SBRT as an alternative treatment modality for elderly patients has increased owing to the availability and development of various stereotactic radiotherapy techniques and equipment.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Several reports have shown that SBRT is a safe and feasible treatment for elderly patients regarding treatment complications and oncological outcomes. 18,[27][28][29][30][31][32][33][34][35][36][37][38] The use of SBRT as an alternative treatment modality for elderly patients has increased owing to the availability and development of various stereotactic radiotherapy techniques and equipment.…”
Section: Introductionmentioning
confidence: 99%